Identify changes of brain regional homogeneity in bipolar disorder and unipolar depression using resting-state FMRI. - Min-Jie Liang; Quan Zhou; Kan-Rong Yang; Xiao-Ling Yang; Jin Fang; Wen-Li Chen; Zheng Huang (PLoS ONE, 2013)
BACKGROUND: To identify changes in brain activation patterns in bipolar disorder (BD) and unipolar depression (UD) patients. METHODOLOGY/PRINCIPAL FINDINGS: Resting-state fMRI scans of 16 healthy controls, 17 BD and 16 UD patients were obtained. T-test of normalized regional homogeneity (ReHo) was performed in a voxel-by-voxel manner. A combined threshold of á = 0.05, minimum cluster volume of V = 10503 mm(3) (389 voxels) were used to determine ReHo differences between groups. In UD group, fMRI revealed ReHo increases in the left middle occipital lobe, right inferior parietal lobule, right precuneus and left convolution; and ReHo decreases in the left parahippocampalgyrus, right precentralgyrus, left postcentralgyrus, left precentralgyrus and left cingulated. In BD group, ReHo increases in the right insular cortex, left middle frontal gyrus, left precuneus, left occipital lobe, left parietal, left superior frontal gyrus and left thalamus; and ReHo decreases in the right anterior lobe of cerebellum, pons, right precentralgyrus, left postcentralgyrus, left inferior frontal gyrus, and right cingulate. There were some overlaps in ReHo profiles between UD and BD groups, but a marked difference was seen in the thalamus of BD. CONCLUSIONS/SIGNIFICANCE: The resting-state fMRI and ReHo mapping are a promising tool to assist the detection of functional deficits and distinguish clinical and pathophysiological signs of BD and UD.